Tinjauan Kriminologi Terhadap Tindak Pidana Pencurian Ternak Di Wilayah Hukum Polda Nusa Tengara Timur - Vita Adolfina Manafe; Hery Firmansyah (Jurnal Pro Hukum : Jurnal Penelitian Bidang Hukum Universitas Gresik, 2023)
This study aims to determine the factors that cause the crime of livestock theft in the jurisdiction of the East Nusa Tenggara Regional Police and to identify and analyze the countermeasures carried out by the East Nusa Tenggara Regional Police. This study uses an empirical research method, as it is known that legal research uses primary data which will be obtained directly through the main source of the nature of this research, namely descriptive which is a writing that provides an overview of the actual situation, the types and techniques of collecting legal material used used in this research is the data collected consists of data that is primary and secondary. Based on the research results, it is known that the factors that influence the crime of livestock theft include internal and external factors. The efforts to tackle the crime of livestock theft have been carried out, namely: forming an intelligence network by the regional police, forming a special investigation team, conducting routine patrols, carrying out field operations, and appealing to the public.